Dual Roles of Tight Junction-associated Protein, Zonula Occludens-1, in Sphingosine 1-Phosphate-mediated Endothelial Chemotaxis and Barrier Integrity - Jen Fu Lee; Qun Zeng; Harunobu Ozaki; Lichun Wang; Arthur R. Hand; Timothy Hla; Eugenia Wang; Menq-Jer Lee (2006)
In this report, sphingosine-1-phosphate (S1P), a serum-borne bioactive lipid, is shown to activate tight-junction-associated protein Zonula Occludens-1 (ZO-1), which in turn plays a critical role in regulating endothelial chemotaxis and barrier integrity. After S1P stimulation, ZO-1 was redistributed to the lamellipodia and cell-cell junctions via the S1P1/Gi/Akt/Rac pathway. Similarly, both endothelial barrier integrity and cell motility were significantly enhanced in S1P-treated cells through the Gi/Akt/Rac pathway. Importantly, S1P-enhanced barrier integrity and cell migration were abrogated in ZO-1 knockdown cells, indicating ZO-1 is functionally indispensable for these processes. To investigate the underlying mechanisms, we demonstrated that cortactin plays a critical role in S1P-induced ZO-1 redistribution to the lamellipodia. In addition, S1P significantly induced the formation of endothelial tight junctions. ZO-1 and α-catenin polypeptides were colocalized in S1P-induced junctional structures; whereas, cortactin was not observed in these regions. Together, these results suggest that S1P induces the formation of two distinct ZO-1 complexes to regulate two different endothelial functions: ZO-1/cortactin complexes to regulate chemotactic response and ZO-1/α-catenin complexes to regulate endothelial barrier integrity. The concerted operation of these two ZO-1 complexes may coordinate two important S1P-mediated functions, i.e. migration and barrier integrity, in vascular endothelial cells. In this report, sphingosine-1-phosphate (S1P), a serum-borne bioactive lipid, is shown to activate tight-junction-associated protein Zonula Occludens-1 (ZO-1), which in turn plays a critical role in regulating endothelial chemotaxis and barrier integrity. After S1P stimulation, ZO-1 was redistributed to the lamellipodia and cell-cell junctions via the S1P1/Gi/Akt/Rac pathway. Similarly, both endothelial barrier integrity and cell motility were significantly enhanced in S1P-treated cells through the Gi/Akt/Rac pathway. Importantly, S1P-enhanced barrier integrity and cell migration were abrogated in ZO-1 knockdown cells, indicating ZO-1 is functionally indispensable for these processes. To investigate the underlying mechanisms, we demonstrated that cortactin plays a critical role in S1P-induced ZO-1 redistribution to the lamellipodia. In addition, S1P significantly induced the formation of endothelial tight junctions. ZO-1 and α-catenin polypeptides were colocalized in S1P-induced junctional structures; whereas, cortactin was not observed in these regions. Together, these results suggest that S1P induces the formation of two distinct ZO-1 complexes to regulate two different endothelial functions: ZO-1/cortactin complexes to regulate chemotactic response and ZO-1/α-catenin complexes to regulate endothelial barrier integrity. The concerted operation of these two ZO-1 complexes may coordinate two important S1P-mediated functions, i.e. migration and barrier integrity, in vascular endothelial cells. Endothelial barrier integrity is an important physiological function of the endothelium in vivo. Dysregulated barrier integrity is implicated in a variety of pathological conditions, such as stroke, inflammation, various immune responses, etc. (1Fenstermacher J.D. Nagaraja T. Davies K.R. Blood Brain Barrier: Drug Delivery and Brain Pathology. Kluwer Academic-Plenum Publishers, New York2000Google Scholar). To elucidate the function and regulation of endothelial barrier integrity, cultured brain microvascular endothelial cells have been widely employed as an in vitro model system to study the blood-brain barrier (BBB) 2The abbreviations used are: BBB, blood-brain barrier; S1P, sphingosine 1-phosphate; S1P1 (old nomenclature EDG-1, endothelial differentiating gene-1), the high affinity GPCR for S1P; ZO-1, Zonula Occludens-1; ECIS, electrical cell-substrate impedance sensing technique; GPCR, G-protein-coupled receptor; si-S1P1, silencing RNA for S1P1 receptor; si-ZO-1, silencing RNA for ZO-1 polypeptide; PTO, phosphothioate oligonucleotide; PECAM, platelet-endothelial cell adhesion molecule; VE-cad, VE-cadherin; PTx, pertussis toxin; moi, multiplicity of infection; JAM, junctional adhesion molecule; TEER, transendothelial electrical resistance. 2The abbreviations used are: BBB, blood-brain barrier; S1P, sphingosine 1-phosphate; S1P1 (old nomenclature EDG-1, endothelial differentiating gene-1), the high affinity GPCR for S1P; ZO-1, Zonula Occludens-1; ECIS, electrical cell-substrate impedance sensing technique; GPCR, G-protein-coupled receptor; si-S1P1, silencing RNA for S1P1 receptor; si-ZO-1, silencing RNA for ZO-1 polypeptide; PTO, phosphothioate oligonucleotide; PECAM, platelet-endothelial cell adhesion molecule; VE-cad, VE-cadherin; PTx, pertussis toxin; moi, multiplicity of infection; JAM, junctional adhesion molecule; TEER, transendothelial electrical resistance. (2Gumbleton M. Audus K.L. J. Pharm. Sci. 2001; 90: 1681-1698Abstract Full Text Full Text PDF PubMed Scopus (250) Google Scholar). Evidence from these studies indicates that BBB plays a critical role in regulating the homeo-static environment of the brain and the transportation of plasma constituents into brain. Furthermore, it has been shown that severely impaired blood-brain barrier integrity is attributed to the pathological states of various neurological disorders, such as multiple sclerosis (3Plumb J. McQuaid S. Mirakhur M. Kirk J. Brain Pathol. 2002; 12: 154-169Crossref PubMed Scopus (207) Google Scholar, 4Rosenberg G.A. Neuroscientist. 2002; 8: 586-595Crossref PubMed Scopus (112) Google Scholar), Alzheimer disease (5Kalaria R.N. Cerebrovasc. Dis. 2002; 13: 48-52Crossref PubMed Scopus (211) Google Scholar, 6Miyakawa T. Ann. N. Y. Acad. Sci. 2002; 977: 303-305Crossref PubMed Scopus (12) Google Scholar), and human immunodeficiency virus-1-associated encephalitis or dementia (7Andersson L.M. Hagberg L. Fuchs D. Svennerholm B. Gisslen M. J. Neurovirol. 2001; 7: 542-547Crossref PubMed Scopus (52) Google Scholar, 8Bussolino F. Mitola S. Serini G. Barillari G. Ensoli B. Int. J. Biochem. Cell Biol. 2001; 33: 371-390Crossref PubMed Scopus (57) Google Scholar).Sphingosine 1-phosphate (S1P), a serum-borne bioactive lipid mediator secreted by activated platelets (9Yatomi Y. Ruan F. Hakomori S. Igarashi Y. Blood. 1995; 86: 193-202Crossref PubMed Google Scholar), enhances barrier formation in cultured pulmonary endothelial cells (ECs) (10Garcia J.G.N. Liu F. Verin A.D. Birukova A. Dechert M.A. Gerthoffer W.T. Bamburg J.R. English D. J. Clin. Investig. 2001; 108: 689-701Crossref PubMed Scopus (736) Google Scholar). However, the molecular details for the formation and maintenance of endothelial barrier integrity are poorly understood. It was recently reported that the association of cortactin, an F-actin cross-linking polypeptide, and myosin light chain kinase is crucial in S1P-enhanced endothelial barrier integrity (11Dudek S.M. Jacobson J.R. Chiang E.T. Birukov K.G. Wang P. Zhan X. Garcia J.G. J. Biol. Chem. 2004; 279: 24692-24700Abstract Full Text Full Text PDF PubMed Scopus (247) Google Scholar). Furthermore, it is well documented that tight junctions are important in regulating BBB formation (12Fanning A.S. Jameson B.J. Jesaitis L.A. Anderson J.M. J. Biol. Chem. 1998; 273: 29745-29753Abstract Full Text Full Text PDF PubMed Scopus (1086) Google Scholar, 13Huber J.D. Egleton R.D. Davis T.P. Trends Neurosci. 2001; 24: 719-725Abstract Full Text Full Text PDF PubMed Scopus (629) Google Scholar). In addition, S1P greatly enhances VE-cadherin (VE-cad)-based adherens junctions in endothelial cells (14Lee M.J. Thangada S. Claffey K.P. Ancellin N. Liu C.H. Kluk M. Volpi M Sha¡ afi R.I. Hla T. Cell. 1999; 99: 301-312Abstract Full Text Full Text PDF PubMed Scopus (859) Google Scholar, 15Lee M.J. VanBrocklyn J.R. Thangada S. Liu C.H. Hand A.R. Menzeleev R. Spiegel S. Hla T. Science. 1998; 279: 1552-1555Crossref PubMed Scopus (881) Google Scholar). Also, platelet-endothelial cell adhesion molecule-1 (PECAM), E-selectin, and intercellular cell adhesion molecules (ICAM) are regulated in endothelial cells with S1P treatment (16Krump-Konvalinkova V. Yasuda S. Rubic T. Makarova N. Mages J. Erl W. Vosseler C. Kirkpatrick J. Tigyi G. Siess W. Arterioscler. Thromb. Vasc. Biol. 2005; 25: 1-7Crossref Scopus (75) Google Scholar). Together, S1P-mediated endothelial barrier function may be the concerted activation of these molecules required for junctional structures and cell-cell interaction.Here we demonstrate that S1P treatment not only significantly increases endothelial barrier integrity, but also greatly enhances cell migration into electrically wounded areas, as determined by electrical cell-substrate impedance sensing technology (ECIS) (17Keese C.R. Wegener J. Walker S.R. Giaever I. Proc. Natl. Acad. Sci. U. S. A. 2004; 101: 1554-1559Crossref PubMed Scopus (344) Google Scholar). In addition, both endothelial barrier integrity and chemotactic response were found to be controlled by the same signaling cascade, i.e. S1P1/Akt/Rac pathway. Thus, it suggests that a common modulator may be present to regulate both responses. In this report, evidence is shown that Zonula Occludens-1 (ZO-1), a tight junction-associated protein, is functionally critical in regulating S1P-mediated endothelial barrier integrity and chemotactic response. Data from this study also suggest that S1P induces the formation of distinct ZO-1 functional complexes, which in turn control the distinct physiological processes of the endothelium.EXPERIMENTAL PROCEDURESMaterials, Cell Culture, and Adenoviral Transduction—Sphingosine 1-phosphate was obtained from Biomol. Pertussis toxin (PTx) and Ly294002 were from Calbiochem. Other reagents, unless specified, were from Sigma. Human Umbilical Vein Endothelial Cells (HUVECs) and Chinese Hamster Ovary (CHO-K1) cells stably expressing the S1P1 receptor were cultured essentially as described (18Lee M.J. Thangada S. Paik J.H. Gopal S.P. Ancellin N. Chan S.S. Wu M. Morales-Ruiz M. Sessa W.C. Alessi D. Hla T. Mol. Cell. 2001; 8: 693-704Abstract Full Text Full Text PDF PubMed Scopus (268) Google Scholar). Human brain microvascular endothelial cells (HBMECs, gift of Dr. Kwang Sik Kim, Johns Hopkins University) were cultured essentially as HUVECs. For adenoviral transduction, cells were infected with adenoviral particles carrying various cDNA constructs for 12 h prior to stimulation with S1P as previously described (18Lee M.J. Thangada S. Paik J.H. Gopal S.P. Ancellin N. Chan S.S. Wu M. Morales-Ruiz M. Sessa W.C. Alessi D. Hla T. Mol. Cell. 2001; 8: 693-704Abstract Full Text Full Text PDF PubMed Scopus (268) Google Scholar, 19Kalman D. Gomperts S.N. Hardy S. Kitamura M. Bishop J.M. Mol. Biol. Cell. 1999; 10: 1665-1683Crossref PubMed Scopus (61) Google Scholar).siRNA-mediated Gene Silencing—To specifically knockdown the endothelial ZO-1 polypeptide, two pairs of sense and anti-sense hairpin oligonucleotides flanked with BamH1 and EcoRI restriction sites at 5′- and 3′-end, respectively, were designed according to the GenScript siRNA sequence design tool (siRNA target finder). The oligonucleotides sequences for the construct 1: (sense): 5′-gatcc GTGAG CAATA TTCAC GCAGT TATTC AAGAG ATAAC TGCGT GAATA TTGCT CACTT TTTTg-3′, (antisense): 5′-aattc AAAAA AGTGA GCAAT ATTCA CGCAG TTATC TCTTG AATAA CTGCG TGAAT ATTGC TCACg-3′; and construct 2: (sense) 5′-gatcc GTTAT TCGCC TGCAT ACAAT AATTC AAGAG ATTAT TGTAT GCAGG CGAAT AACTT TTTTg-3′, (antisense): 5′-aattc AAAAA AGTTA TTCGC CTGCA TACAA TAATC TCTTG AATTA TTGTA TGCAG GCGAA TAACg-3′. The sense and antisense oligonucleotides were annealed and cloned into the Lentiviral pFIV-H1 vector (System Bioscience). Lentiviral transducing particles were produced by packaging in the 293T/17 cell line following the manufacturer's instructions. Lentiviral particles carrying the siRNA oligonucleotide for luciferase were used as a control in this study. HUVECs (6 × 105 cells) were infected with Lentiviral particles (∼0.1 moi) in 60-mm dishes for 24 h in the presence of polybrene (2 μg/ml), washed and replaced with fresh medium for additional 24 h. Subsequently, cells were split (1:3 split ratio), and stably transduced HUVECs were isolated with Puromycin (1 μg/ml) selection. In addition, two pairs of oligonucleotides were used to knockdown S1P1 receptor, the construct 23: (sense) 5′-gatcc GCACT ATATC CTCTT CTGCT TCAAG AGAGC AGAAG AGGAT ATAGT GCTTT TTTg-3′, (antisense) 5′-aattc AAAAA AGCAC TATAT CCTCT TCTGC TCTCT TGAAG CAGAA GAGGA TATAG TGCg-3′; the construct 24: (sense) 5′-gatcc GTCTA CTCCT TGGTC AGGAC TTCAA GAGAG TCCTG ACCAA GGAGTAGATT TTTTg-3′, (antisense) 5′-aattc AAAAA ATCTA CTCCT TGGTC AGGAC TCTCT TGAAG TCCTG ACCAA GGAGT AGACg-3′.Immunofluorescence Analysis—Recently confluent HUVECs (3 × 105 cells in 35-mm glass bottom dishes, MatTek) were serum-starved in plain M199 medium for 2 h, followed by stimulation with S1P (500 nm, 30 min). Cells were fixed with 4% paraformaldehyde, permeabilized with 0.25% Triton X-100, and immunostained with the indicated primary antibodies overnight. Following incubation with Alexa488- or Alexa594-conjugated secondary antibodies (Molecular Probes), the stained images were visualized and photographed with the Axiovert 200 m epi-fluorescence microscope (Carl Zeiss).Western Blot Analysis—Proteins were separated on 10% SDS-PAGE and transferred to nitrocellulose membranes. After blocking with 5% nonfat milk, the membranes were blotted with 1 μg/ml of ZO-1 (Zymed Laboratories Inc.) or cortactin antibody (4F11, Upstate). Subsequently, the nitrocellulose membranes were incubated with their corresponding horseradish peroxidase-conjugated secondary antibody (Pierce) and visualized using the ECL method (Amersham Biosciences).Phosphothioate Oligonucleotide Transfection—The following 15-mer phosphothioate oligonucleotide (PTO) was synthesized to block the expression of cortactin polypeptide: antisense cortactin, 5′-AGCGT GGCCT GCTGA-3′. The sense PTO, 5′-TCAGC AGGCC ACGCT-3′, was used as a control. For PTO transfection, HBMECs (2 × 106 in a 100-mm dish) were co-transfected with PTO (100 nm) and cDNA vector of green fluorescent protein (GFP, 8 μg) (15Lee M.J. VanBrocklyn J.R. Thangada S. Liu C.H. Hand A.R. Menzeleev R. Spiegel S. Hla T. Science. 1998; 279: 1552-1555Crossref PubMed Scopus (881) Google Scholar) for overnight by Lipofectamine reagent. Subsequently, cells were serum-starved in medium M199 supplemented with 0.5% FBS for 24 h. After stimulating without or with S1P (500 nm) for 30 min, cells were subjected to immunoblot or immunostaining as described above.Transmission Electron Microscopy—HUVECs (1 × 105 cells) were plated in tissue culture flasks (12.5 cm2, Falcon). Three days later, cells were starved in plain M199 for 2 h, followed by stimulating without or with S1P (500 nm, 30 min). Cells were fixed in 2.5% (v/v) glutaraldehyde in 0.1 m sodium cacodylate buffer (pH 7.4), postfixed in 1% osmium tetroxide-0.8% potassium ferricyanide in cacodylate buffer, treated with 0.5% aqueous uranyl acetate and embedded in epoxy resin. Thin sections were cut with a diamond knife, stained with uranyl acetate and lead citrate and observed in a Philips CM10 electron microscope at 60 kV.Electrical Cell Substrate Impedance Sensing (ECIS) Assay—ECIS™ Model 1600R (Applied BioPhysics) was used to measure the transendothelial electrical resistance (TEER) in confluent or electrically wounded endothelial cells to study the S1P-regulated barrier integrity and migratory response, respectively (17Keese C.R. Wegener J. Walker S.R. Giaever I. Proc. Natl. Acad. Sci. U. S. A. 2004; 101: 1554-1559Crossref PubMed Scopus (344) Google Scholar). Briefly, to study the endothelial integrity function, 200 μl of cell suspension (5 × 105 cells per ml) were seeded to each well of either a 8W1E or 8W10 ECIS array (one electrode or 10 electrodes per well, respectively), which was pre-equilibrated with 200 μl of medium at 37 °C for 30 min. 2-3-days later, endothelial cells were serum-starved in plain M199 medium for 2 h at 37 °C. After stimulation with S1P, the endothelial integrity function was measured in real-time as described (17Keese C.R. Wegener J. Walker S.R. Giaever I. Proc. Natl. Acad. Sci. U. S. A. 2004; 101: 1554-1559Crossref PubMed Scopus (344) Google Scholar). For migratory response, the cell-covered electrode was connected to an AC source. By applying 5 volts for 30 s, a relatively high current was delivered to the cell-covered electrode and killed the cells on the electrode (250 μm diameter) (17Keese C.R. Wegener J. Walker S.R. Giaever I. Proc. Natl. Acad. Sci. U. S. A. 2004; 101: 1554-1559Crossref PubMed Scopus (344) Google Scholar). Thereafter, endothelial migratory responses were determined in real-time by measuring the recovery of electrical impedance, an indicator of the surrounding viable endothelial cells migrating into the wounded area, in the presence or absence of S1P treatment.Migration Assay—Endothelial chemotaxis was measured by using the transwell migration assay (8 μm pore size, Costar) as described (18Lee M.J. Thangada S. Paik J.H. Gopal S.P. Ancellin N. Chan S.S. Wu M. Morales-Ruiz M. Sessa W.C. Alessi D. Hla T. Mol. Cell. 2001; 8: 693-704Abstract Full Text Full Text PDF PubMed Scopus (268) Google Scholar). Briefly, polycarbonate membranes were coated with human fibronectin (1 μg/ml) for overnight at 4 °C. Following serum starvation, HUVECs were trypsinized, counted, and resuspended in M199 media with 0.5% fatty-acid free bovine serum albumin (Sigma). Cells (7.5 × 104 cells in 100 μl) were placed in the upper chamber and media (600 μl) containing various concentrations of S1P were added to the lower chamber. Endothelial cells were allowed to migrate for 4 h at 37 °C in a humidified chamber with 5% CO2. Subsequently, the nonmigrated cells on the upper side of the filter were removed with a cotton swab. The filters were fixed with 4% formaldehyde and stained with 0.1% crystal violet solution. Following eluting the stained dye with 10% acetic acid, cell chemotaxis was quantitated with BMG FluoStar Galaxy microplate reader (BMG Labtechnologies) at A590 nm.Statistic Analysis—Student's t test was used for statistic analysis. p-value < 0.001 was considered as statistically significant.RESULTSTo study the dynamic behavior of endothelial cells in culture, the ECIS was used to measure the S1P-regulated TEER in real time (17Keese C.R. Wegener J. Walker S.R. Giaever I. Proc. Natl. Acad. Sci. U. S. A. 2004; 101: 1554-1559Crossref PubMed Scopus (344) Google Scholar). In this technology, as endothelial cells attach and spread on the small gold film electrode of the ECIS array, cellular membranes restrict the electrical current, forcing it to flow beneath and between the cells, resulting in a dramatic increase in electrical impedance (Fig. 1a). Furthermore, the endothelial cells attached to the circular microelectrode (250-μm diameter) can be selectively killed by applying a high voltage electrical current (5 volts for 30 s, arrowhead in Fig. 1a). The efficiency of this electrical current to completely kill endothelial cells attached to the microelectrode was shown by an abrupt drop of electrical impedance (Fig. 1a) and was verified by microscopic observation (panels I and II, Fig. 1b). Subsequently, the viable cells surrounding the wounded microelectrode were allowed to migrate into the electrically wounded area, and reestablished the cell-cell interaction over the electrode (panels III and IV, Fig. 1b). The kinetics for this sequence of events can be monitored in real-time by the increase of electrical impedance (Fig. 1a).We utilized the ECIS technique to monitor the spatial and temporal behavior of S1P-regulated migration in repairing the endothelial injury. Endothelial cells attached to the circular microelectrodes were killed by elevating electrical current and the surrounding viable cells were allowed to migrate into the wounded area in the presence or absence of S1P. As shown in Fig. 2a, S1P treatment significantly increased the TEER in the electrically injured endothelial monolayers. Microscopic examination showed that the raised TEER correlated well with the numbers of cells migrated into the wounded area (Fig. 2b). Moreover, this S1P effect on cell motility was markedly diminished in S1P1 knockdown ECs (si-S1P1) (Fig. 2c), indicating S1P1 receptor play a critical role in this process. The reduced but detectable S1P-responsiveness in si-S1P1 cells may be caused by the residual S1P1 receptor in knockdown cells (Fig. 2e). It was shown that S1P is able to activate Akt and Rac GTPase in endothelial cells (18Lee M.J. Thangada S. Paik J.H. Gopal S.P. Ancellin N. Chan S.S. Wu M. Morales-Ruiz M. Sessa W.C. Alessi D. Hla T. Mol. Cell. 2001; 8: 693-704Abstract Full Text Full Text PDF PubMed Scopus (268) Google Scholar), and S1P-regulated cytoskeletal remodeling and chemotactic response are dependent on Akt and Rac activities (14Lee M.J. Thangada S. Claffey K.P. Ancellin N. Liu C.H. Kluk M. Volpi M Sha¡ afi R.I. Hla T. Cell. 1999; 99: 301-312Abstract Full Text Full Text PDF PubMed Scopus (859) Google Scholar, 18Lee M.J. Thangada S. Paik J.H. Gopal S.P. Ancellin N. Chan S.S. Wu M. Morales-Ruiz M. Sessa W.C. Alessi D. Hla T. Mol. Cell. 2001; 8: 693-704Abstract Full Text Full Text PDF PubMed Scopus (268) Google Scholar). As shown in Fig. 2d, the S1P-induced cell migration in ECIS wound-healing assay required Akt and Rac activities, because transduction with adenoviral particles carrying dominant-negative -Akt and -Rac polypeptides completely inhibited endothelial migration to repair the wounds; whereas, transduction with control β-galactosidase particles had no effect (Fig. 2, c and d).FIGURE 2S1P accelerates endothelial migration in ECIS wounding assay. a, endothelial cells on the micro-electrodes of the ECIS wells were killed with a high electrical voltage as described. Subsequently, the migration of viable cells into the wounded microelectrodes was measured in real-time by electrical impedance in the presence or absence of S1P (500 nm). b, micrographs of ECIS arrays, taken at 3 h after electrical injury. -S1P and +S1P, without or with S1P addition, respectively. Scale bar, 125 μm. c, cell migration in ECIS wounding assays was performed in endothelial cells stably transduced with si-RNA for S1P1 (si-S1P1) or Luciferase (si-Luc) with or without S1P stimulation. d, endothelial cells were transduced with adenoviral particles carrying β-galactosidase (β-gal), dominant negative -Akt (dnAkt), and -Rac (dnRac) cDNAs as described (200 moi each) (18Lee M.J. Thangada S. Paik J.H. Gopal S.P. Ancellin N. Chan S.S. Wu M. Morales-Ruiz M. Sessa W.C. Alessi D. Hla T. Mol. Cell. 2001; 8: 693-704Abstract Full Text Full Text PDF PubMed Scopus (268) Google Scholar). After killing the cells on the microelectrodes, the migratory responses were measured with or without S1P treatment. e, 50 μg of extracts from endothelial cells transduced with si-Luc and two different si-S1P1 constructs (23 and 24) were directly immunoblotted with anti-S1P1 (upper panel). Lower panel, 500 μg of extracts were immunoprecipitated with anti-S1P1 followed by immunoblotting with anti-S1P1. Densitometric quantitation showed that ∼80 and 60% of S1P1 were knocked-down in si-S1P1 23 and 24 transduced endothelial cells. Middle panel, Western blot with anti-actin showed the protein equal loading and the absence of off-target effect by si-S1P1 silencing. f, in a parallel experiment, endothelial cells were transduced with 200 moi of adenoviral particles as described in panel d. 500 μg of cell extracts were immunoprecipitated with anti-S1P1, followed by immunoblotting with anti-S1P1 (top panel). Alternatively, 50 μg of extracts were immunoblotted with anti-Akt or anti-Myc to show the expression of transduced polypeptides (middle and lower panels) (18Lee M.J. Thangada S. Paik J.H. Gopal S.P. Ancellin N. Chan S.S. Wu M. Morales-Ruiz M. Sessa W.C. Alessi D. Hla T. Mol. Cell. 2001; 8: 693-704Abstract Full Text Full Text PDF PubMed Scopus (268) Google Scholar, 19Kalman D. Gomperts S.N. Hardy S. Kitamura M. Bishop J.M. Mol. Biol. Cell. 1999; 10: 1665-1683Crossref PubMed Scopus (61) Google Scholar). Left lane, without endothelial extracts. The arrows in panels a, c, and d are when cells on the microelectrodes were killed by elevating the voltage, followed by stimulation with or without S1P. Panels a, c, and d are mean ± S.E. of two determinants from a representative experiment, which has been repeated at least three times with identical results.View Large Image Figure ViewerDownload Hi-res image Download (PPT)Two alternative approaches were employed to confirm the capability of the S1P1/Akt/Rac pathway in regulating cell motility to repair the endothelial injury. As shown in Fig. 3a, S1P significantly enhanced endothelial migration in the transwell migration assay, and S1P-induced chemotaxis was markedly reduced in S1P1 knockdown endothelial cells. Moreover, transduction with dominant-negative Akt and Rac completely abrogated S1P-induced chemotactic response (Fig. 3b). In a control, transduction with β-galactosidase had no effect on S1P-enhanced endothelial chemotaxis. In addition, a small scrape wound was made across a confluent monolayer of HUVEC and cell migration into the denuded area was measured (Fig. 3c). S1P treatment significantly accelerated cell migration into the wounded area; whereas, wound closure in the absence of S1P was retarded (Fig. 3c, upper panels). Furthermore, the denuded area remained unpopulated in dominant-negative Akt and Rac transduced cells after S1P stimulation (Fig. 3c, lower panels). In a control, the denuded area was repopulated by β-galactosidase transduced endothelial cells in the presence of S1P treatment (Fig. 3c, middle panel). These results together suggest that the S1P-activated S1P1/Akt/Rac pathway is capable of enhancing cell motility to repair the injured endothelial monolayer.FIGURE 3S1P-mediated signaling regulates endothelial migration. a, chemotactic responses were measured by transwell migration assay as described under "Experimental Procedures." Note that S1P-induced chemotactic responses were significantly inhibited in both construct 23 and 24 si-S1P1 endothelial cells. b, Transwell migration assays were performed with ECs transduced with Adenoviral particles carrying β-galactosidase, dominant-negative -Akt and -Rac vectors in the presence or absence of S1P stimulation. The data in a and b are the mean ± S.E. of three determinants from a representative experiment, which was repeated two times with similar results. c, phase contrast micrographs show the S1P-enhanced repair of endothelial injuries. Wounds were introduced in confluent monolayers of wild-type (upper panels), β-galactosidase (middle panels), dominant-negative Akt or Rac (lower panels) transduced cells with sterile microtips. After stimulation without or with S1P for 16 h, cells were fixed. The distances (numbers in upper right, μm) between two edges of wounds were quantitated with a Zeiss microscope equipped with Axiovert image software (Carl Zeiss). The data are the mean ± S.E. of 6 microscopic fields from two determinants, which were repeated three times with similar results.View Large Image Figure ViewerDownload Hi-res image Download (PPT)We next utilized the ECIS assay to examine the effects of S1P on cell-cell interaction in confluent endothelial monolayers. As shown in Fig. 4a, a robust increase of TEER was observed immediately after S1P treatment, indicating that S1P was able to enhance endothelial cell-cell interaction. The S1P-induced cell-cell interaction was sustained for more than 6-10 h after S1P treatment and thus was not a transient event. S1P-enhanced TEER was markedly abrogated in S1P1 knockdown endothelial cells (si-S1P1), and not in control cells stably expressing si-RNA for luciferase (si-Luc) (Fig. 4b). This indicates that S1P-enhanced TEER is primarily controlled by the endothelial S1P1 receptor. This conclusion was supported by the observation that S1P-enhanced endothelial barrier integrity was abrogated in the presence of pertussis toxin (PTx, Fig. 4c), as S1P1 signaling is dependent on the Gi heterotrimeric G protein. Previously it was shown that S1P1 signaling activates the PI 3-kinase (PI3K)/Akt/Rac pathway to regulate endothelial chemotaxis and morphogenesis (18Lee M.J. Thangada S. Paik J.H. Gopal S.P. Ancellin N. Chan S.S. Wu M. Morales-Ruiz M. Sessa W.C. Alessi D. Hla T. Mol. Cell. 2001; 8: 693-704Abstract Full Text Full Text PDF PubMed Scopus (268) Google Scholar). Therefore, we examined whether PI3K/Akt/Rac signaling controls S1P-mediated TEER. As shown in Fig. 4d, treatment with Ly294002, an inhibitor of PI3K, or adenoviral particles carrying dominant-negative Akt or Rac constructs, significantly inhibited the S1P-enhanced TEER. Together, these results indicate that S1P-enhanced intercellular interaction is controlled by the S1P1-mediated Gi/PI3K/Akt/Rac signaling pathway.FIGURE 4S1P signaling enhances transendothelial electrical resistance and induces tight junction formation. a, the TEER, an indicator of endothelial integrity function (10Garcia J.G.N. Liu F. Verin A.D. Birukova A. Dechert M.A. Gerthoffer W.T. Bamburg J.R. English D. J. Clin. Investig. 2001; 108: 689-701Crossref PubMed Scopus (736) Google Scholar, 17Keese C.R. Wegener J. Walker S.R. Giaever I. Proc. Natl. Acad. Sci. U. S. A. 2004; 101: 1554-1559Crossref PubMed Scopus (344) Google Scholar), was measured in